Effects of Yoga Nidra to Enhance Self-Confidence and Reduce Anxiety Among Female Athletes - Kanchana, D.; Senthil Kumar, M. (Journal of Neonatal Surgery, 2025)
There can be seen a variety of obstacles such as overtraining, competing and training times, stress, academic responsibilities and travel are some of the challenges that are influencing athletes' performance. The study investigates the effect of Yoga Nidra in enhancing self-confidence and reducing anxiety among female athletes. For the study, a pre- and post-test randomized design had been applied. According to the inclusion criteria, 82 female athletes (age 18-23 years) have been selected. In the experimental group, participants had participated in a Yoga Nidra program for 12 weeks where they had to attend 3 session every week. The Yoga Nidra sessions emphasized baring the mind, being aware of oneself, and using positive mental images to bolster self-belief and combat anxiety. On the other hand, no intervention had been offered to the control group participants though, it had been suggested they continue with their normal training regimes. As a result, Yoga Nidra can reduce anxiety in the experimental group significantly and meaningfully opposed to the control group. Yoga Nidra importance is suggested by many anxiety levels explained in the model for the anxiety management techniques.